2019
DOI: 10.1111/chd.12830
|View full text |Cite
|
Sign up to set email alerts
|

Ductus arteriosus‐associated infective endarteritis: Lessons from the past, future perspective

Abstract: Background Since routine clinical use of antibiotics as well as surgical and catheter‐based closure of a patent arterial duct (PDA), PDA‐associated infective endarteritis (PDA‐IE) is rare but can still occur when the ductus is still open or as it closes. Thus, clinicians should maintain a high index of concern for patients with unexplained fever. Methods We report on a PDA‐IE in a young infant shortly after potentially delayed obliteration of a PDA. We discuss this case report by reviewing the literature in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Another study reported infective endarteritis as a complication of PDA in 14 children over six years; most of these patients had small PDAs [ 11 ]. PDA-associated endarteritis is rare but can occur when the duct is still open or as it closes [ 12 ]. Patrícia Sá Ferreira et al reported an infant with Kleibsella endarteritis concerning a silent PDA [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported infective endarteritis as a complication of PDA in 14 children over six years; most of these patients had small PDAs [ 11 ]. PDA-associated endarteritis is rare but can occur when the duct is still open or as it closes [ 12 ]. Patrícia Sá Ferreira et al reported an infant with Kleibsella endarteritis concerning a silent PDA [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of arterial infection endarteritis in patients with PDA has decreased because of improved dental and health care, widespread use of broad-spectrum antibiotics, and increased frequency of PDA closure using an interventional occluder device [ 1 ]. However, endarteritis can still occur, particularly with a small or silent PDA [ Figure 5 ] [ 14 , 15 , 16 , 17 , 18 , 19 ]. Turbulent flow secondary to abrupt change in diameter and pressure through the small PDA may lead to formation of endarteritis at the pulmonic end of PDA.…”
Section: Potential Role Of Ct In the Diagnosis Of Pdamentioning
confidence: 99%
“…In addition to the hemodynamic impact of the left-to-right shunt in patients with PDA, the risk of infective endocarditis (IE) is increased [3]. In the past, antibiotic IE prophylaxis (AP) was recommended in risk situations for transient bacteremia.…”
Section: Introductionmentioning
confidence: 99%